Kehidupan Sosial Ekonomi Petani Karet di Nagari Sumpur Kudus Selatan Kecamatan Sumpur Kudus Kabupaten Sijunjung Tahun 2007-2022 - Fani kurnia; Azmi Fitrisia (Jurnal Kronologi, 2023)
The research entitled socio-economic life of rubber farmers in Nagari Sumpur Kudus Selatan, Kecamatan Sumpur Kudus Kabupaten Sijunjung regency in 2007-2022. The thesis majoring in history education, faculty of social sciences, padang state university raises the issue of how to develop the socio-economic life of rubber farmers in Nagari Sumpur Kudus Selatan, Sumpur Kudus District, district Sijunjung regency in 2007-2022. This study uses a qualitative appoarch to the research method, namely the historical method consist or data collection. The second stage is source critism, namely the author examines whether the data that has been found is true or not, whether the source is really good and reliable. The tird stage, interpretation, the fourth stage historiography namely the author writes from the data. The data that has been optained becomes a scientific work. The results of this study found that the main livelihood of the people of Nagari Sumpur Kudus Selatan is as rubber farmers, where rubber plants entered the Nagari around the 1940s and have continued to develop until now.